Analysis of the content of the applied fifth grade chemistry book according to life skills - Dr.Anwar Abbas Mohammed Al Jurani, Turki Jassim Abdullah AL Khalidi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to analyze the chemistry books for the preparatory stage according to life skills for the academic year (2019-2020) and to know the life skills contained in the chemistry books for the preparatory stage through the following two questions:1-What life skills should be available in the content of chemistry books prescribed for middle school students approved by the Ministry of Education, General Directorate of Curricula in the academic year(2019-2020). 2-What is the percentage of life skills included in the content of chemistry textbooks prescribed for middle school students approved by the Ministry of Education, General Directorate of Curricula in the academic year (2019-2020).